2011
DOI: 10.1152/ajpcell.00179.2010
|View full text |Cite
|
Sign up to set email alerts
|

Role of integrins in angiotensin II-induced proliferation of vascular smooth muscle cells

Abstract: Angiotensin II (AII) binds to G protein-coupled receptor AT(1) and stimulates extracellular signal-regulated kinase (ERK), leading to vascular smooth muscle cells (VSMC) proliferation. Proliferation of mammalian cells is tightly regulated by adhesion to the extracellular matrix, which occurs via integrins. To study cross-talk between G protein-coupled receptor- and integrin-induced signaling, we hypothesized that integrins are involved in AII-induced proliferation of VSMC. Using Oligo GEArray and quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…These results were consistent with our previous findings using human aortic SMCs (13). Therefore, it was shown that the In fact, angiotensin II causes VSMC proliferation and migration, an increase in matrix production of fibronectin and collagen, and induction of oxidative stress (2,31,35). In this study, pulsatile pressure stress increased proliferation and migration.…”
Section: Methodssupporting
confidence: 93%
“…These results were consistent with our previous findings using human aortic SMCs (13). Therefore, it was shown that the In fact, angiotensin II causes VSMC proliferation and migration, an increase in matrix production of fibronectin and collagen, and induction of oxidative stress (2,31,35). In this study, pulsatile pressure stress increased proliferation and migration.…”
Section: Methodssupporting
confidence: 93%
“…AngII induces smooth muscle adhesion to collagen and fibronectin through the AT1 receptor [192194], resulting in FAK-dependent ERK activation and enhanced cell proliferation [195, 196]. Cytoskeletal stiffening and contraction of smooth muscle cells treated with AngII results in elevated blood pressure [192, 193, 197], thereby enhancing mechanical load on the smooth muscle integrins.…”
Section: Integrins In Smooth Muscle Migration and Proliferationmentioning
confidence: 99%
“…However, integrin signaling may also contribute to vasoconstriction, as treatment with the integrin inhibitor RGDS reduced vasoconstriction to AngII but not other vasoconstrictors [198]. While α1β1 has largely been implicated in maintaining the contractile phenotype in atherosclerosis, smooth muscle hypertrophy to chronic AngII stimulation is reduced in α1 knockout mice [199], and inhibiting α1β1 using siRNA knockdown or peptide inhibitors blunts AngII-induced ERK activation and proliferation [195, 200]. Consistent with this association, AngII promotes α1 integrin expression [199] along with the expression of multiple provisional matrix-binding integrins, such as α8, β1, and β3 [201, 202].…”
Section: Integrins In Smooth Muscle Migration and Proliferationmentioning
confidence: 99%
“…In addition to their function as a scaffold, ECM proteins also modulate a variety of cellular functions, including migration, differentiation, and proliferation. For example, ASM cells cultured on fibronectin or collagen Type I matrices show enhanced mitogenic responses to growth factors such as platelet-derived growth factor (PDGF) (7)(8)(9)(10)(11)(12). The interaction of these cells with the ECM occurs mainly through integrins, a group of heterodimeric transmembrane glycoproteins.…”
mentioning
confidence: 99%
“…The interaction of these cells with the ECM occurs mainly through integrins, a group of heterodimeric transmembrane glycoproteins. Studies on the role of integrins in smooth muscle cell proliferation have indicated an important role for these ECM receptors (e.g., both the angiotensin II-induced and PDGF-induced proliferation of vascular smooth muscle cells requires signaling through a5b1 integrins) (7,13). In addition, the proliferation of human ASM cells can also be mediated by integrins, in particular by the a5b1 integrins (9,14,15).…”
mentioning
confidence: 99%